Pesan Dakwah Melalui Wacana Kritis dalam Novel Kekasih Impian Karya Wardah Maulina - Oky Octaviani Pakaya; Ellyana Hinta; Herson Kadir (Ideas Publishing, 2022)
The critical discourse of Van Dijk consists of three components, including text, social cognition, and social context. It is utilized in analyzing the da’wah message in WardahMaulina's novel Kekasih Impian. The study objective was to describe the da’wah message through text analysis, social cognition, and social context. It applied to qualitative descriptive. The result revealed that the most found message of da'wah through text analysis is about faith and morals, while social cognition is related to boundary towards someone we have affection with, and in terms of social context, is correlated to piety is the key of present and afterlife happiness.